Modeling Intercultural Communication; An Analysis of the Communication Experience of Migrants with Betawi People - Octavian, Indri; Yuliawati, Elly; Ridaryanthi, Melly (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
Intercultural communication is something unique because of the diversity of thinking patterns and experiences they have, as well as the communication process and interactions between individuals that occur not only in different cultures but also in different languages, values, norms, customs and attitudes. For this reason, this study discusses the perspective of migrants regarding their communication experience with the object of research, namely the Betawi people in Kalideres, which is certainly different and produces a meaning from the experience. This research uses phenomenological method with qualitative approach. The research findings state that there are three stages of experience: 1) the initial experience of becoming a migrant and communicating with the Betawi people in Kalideres is an experience of the adaptation process, 2) the experience after a long stay is a pleasant experience that produces a pleasant positive meaning and  3) the experience of entering into the culture is a pleasant and familial experience that produces a pleasant positive meaning and familial nature. The research concludes that both experience and meaning become a process that cannot be molded but emerges on its own, influenced by the culture and environment that is the context in this study.